Conceptualizing English Workplace Communication Needs of Professional Engineers: The Challenges for English Language Tertiary EducatorS - Abdullah Adnan, Mohamed; Noor Raha, Mohd Radzuan; Hafizoah, Kassim; Mohammad Musab, Azmat Ali (Universiti Selangor, 2014)
Mastery of English oral communication skills is an advantage to employees in their workplaces. In the engineering industry, professional engineers possessing English oral communication skills are at an advantage; either for executing daily tasks or for promotion and career advancement. This paper aims to conceptualize and highlight the communicative events whereby engineers need to have a set of appropriate English communication skills in order to function well in their workplaces. At the same time, this poses great challenges for English language educators in the Malaysian Higher institutions whereby they must train and equip engineering undergraduates with adequate English communication skills in order for them to function effectively in their future engineering workplaces and to tackle the issue of graduate unemployment as a result of lack of English communication skills.